Energetic and exergetic evaluation of the hybridization of Solar Combined Cycle Power Plants - Karellas, Sotirios; Kalogirou, Soteris A.; Lappas, Anastasios; Papadopoulos, Athanasios; Kakaras, Emmanuel (My University, 2015)
The economic crisis, high fuel prices, high generation costs, environmental considerations and international guidelines on carbon emissions have been a strong driver for the increasing exploitation of the use of renewable energy, or hybridization of fossil fired plans. The high levels of Direct Normal Irradiance (DNI) of these countries led them to consider hybridizing existing power plants with concentrated solar energy, substituting natural gas or diesel oil. The Integrated Solar Combined Cycle System (ISCCS) is one of the most promising hybrid configurations for substitution of part of the fossil fuel by efficiently converting solar energy into electricity. The scope of this paper is to simulate and compare energetically and exergetically the potential of hybridizing two Combined Cycle Power Plants (CCPP) in different areas of the Mediterranean region. The plant considered is located in Thisvi, Voiotia, Greece, and is natural gas-fired and is owned and operated by Elpedison. The Concentrating Solar Power technology (CSP) which was chosen to integrate the above mentioned Combined Cycle is basically a solar tower using molten salt as working fluid. The designed solar field layout is based on a methodology presented on recent published studies and the final computations are performed with the IPSEpro software. This study takes into account a wide range of parameters such as different tower heights, heliostat field layouts, heliostat dimensions and DNI values. In addition, a Thermal Energy Storage (TES) configuration was considered, in order to store the excessive solar thermal energy and deliver it back during the absence of irradiation. In conclusion, an economic analysis is conducted and indicates that there are substantial gains to be obtained in ISCC plants through solar contribution, both in power plant efficiency and fuel savings.
Keywords: Integrated Solar Combined Cycle (ISCC); Solar tower; Combined cycle; Hybridization; Thermal Energy Storage (TES)